Handbook of Research Methods and Applications in Economic Geography 2015
DOI: 10.4337/9780857932679.00022
|View full text |Cite
|
Sign up to set email alerts
|

Methods of analyzing the relationship between new business formation and regional development

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…1 shows, the impact of new firms on employment growth is not stable over time, with immediate positive effects being followed by short-term negative effects and again by long-term positive effects. Both positive and negative impacts on employment growth are therefore likely to occur, depending on the time lag of the start-up cohort and a number of studies have confirmed this short-, mediumand long-term pattern (Storey 1994;Fritsch andNoseleit 2009, 2013a, b;Andersson and Noseleit 2011;Koster 2011;Li et al 2011). Fritsch (2008) When new businesses enter a market, they may have both direct and indirect effects on employment development (Fritsch and Mueller 2004).…”
Section: Impact Over Timementioning
confidence: 99%
See 3 more Smart Citations
“…1 shows, the impact of new firms on employment growth is not stable over time, with immediate positive effects being followed by short-term negative effects and again by long-term positive effects. Both positive and negative impacts on employment growth are therefore likely to occur, depending on the time lag of the start-up cohort and a number of studies have confirmed this short-, mediumand long-term pattern (Storey 1994;Fritsch andNoseleit 2009, 2013a, b;Andersson and Noseleit 2011;Koster 2011;Li et al 2011). Fritsch (2008) When new businesses enter a market, they may have both direct and indirect effects on employment development (Fritsch and Mueller 2004).…”
Section: Impact Over Timementioning
confidence: 99%
“…For the purpose of this study, we are mainly concerned with the impact of start-up rates on employment change. However, given that the opposite relationship can be expected to hold as well, a one directional analysis could lead to biased results, overestimating the effect of start-ups if not estimated simultaneously (Fritsch 2015). A number of studies have attempted to disentangle this relationship, most extensively that by Hartog et al (2010) who provide an overview of studies examining this issue and they only find a weak effect of growth in previous periods on the level of new business formation.…”
Section: Dual Causalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous observers claim these indirect effects-costs reductions, the departure of inefficient firms, new products and processes, and greater variety in goods and services-are critical because they promote competitiveness on the supply side of the market and thereby induce further economic development [50,51]. Baumol et al [52] claim that entrepreneurial capitalism (radical innovations, marketing new products) and big-firm capitalism (incremental innovations, scale economies for old products) are both indispensable to the operation of advanced economic systems.…”
Section: Entrepreneurshipmentioning
confidence: 99%